High Performance Grouping With Load Balancing Scheme for Wireless Sensor Networks - T.Jayasankar, M.Sujatha, N.B.Prakash, G.R.Hemalakshmi (International Journal of Advanced Science and Technology, 2019)
In wireless sensor networks (WSNs), the measuring device nodes have restricted power, small computational boundary and fewer memorial. Payable to non-replaceable and non-battery-powered belongings of sensor hub battery, it has been a noteworthy test to diminish the power utilization in power compelled WSNs. Our proposed system is in regards of context of WSN, the weight work utilized for the group-heads (CHs) race is commonly constructed on the residual energy (RE) of the sensors. Be that as it may, compelling into version just the RE as the fundamental CHs decision measure. The experimental consequences exhibited the betterment of the planned technique finished the associated methods.